2018
DOI: 10.1021/acs.iecr.8b00966
|View full text |Cite
|
Sign up to set email alerts
|

A Mass-Transfer Model of Nitric Oxide Removal In a Rotating Drum Biofilter Coupled with FeII(EDTA) Absorption

Abstract: The biological nitric oxide (NO) reduction rate in a rotating drum biofilter (RDB) mainly depends on the mass transfer between the gas and liquid phase because of the poor solubility of NO. This work, aimed to facilitate the gas−liquid (GL) mass transfer of NO in RDB, the Fe II (EDTA) was used to capture NO and porous drum was employed to increase the eddy current effect of the system. The denitrification rate of GL-RDB was stabilized at about 95% during the long-term operation. A dynamic model of GL-RDB was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Other studies have shown that N 2 O accumulation was inhibited with a high C/N ratio, sufficient electron donor and a low sulfite concentration [45]. However, N 2 as the final product of Fe(II)EDTA-NO reduction was recognized by most researchers [7][8][9][10][11]13,20,35,37,38,[45][46][47].…”
Section: Analysis Of Reduction Products Of Fe(ii)edta-nomentioning
confidence: 99%
“…Other studies have shown that N 2 O accumulation was inhibited with a high C/N ratio, sufficient electron donor and a low sulfite concentration [45]. However, N 2 as the final product of Fe(II)EDTA-NO reduction was recognized by most researchers [7][8][9][10][11]13,20,35,37,38,[45][46][47].…”
Section: Analysis Of Reduction Products Of Fe(ii)edta-nomentioning
confidence: 99%
“…Tables 1 and 2 show that organic compounds, such as methanol, ethanol, and glucose, are the most studied electron donors in CABR systems. More specifically, glucose is the most widely used electron donor, with an RE NO above 90% (Chen et al, 2018;Dong et al, 2013;Zhang et al, 2018); however, it is much more expensive than ethanol or methanol. Moreover, glucose concentration and its metabolite products can affect NO RE (Dong et al, 2013).…”
Section: Biological Reduction Of No Contained In Iron Chelatesmentioning
confidence: 99%
“…CABR systems are strongly affected by EBRT; however, increasing the EBRT in bioreactors is not economically viable, while reducing it can cause debilitation of microbial activity and acceleration of the consumption of Fe(II)EDTA 2− , leading to an increase in operational costs and a decrease in the reaction time (Chen et al, 2018). Lu et al (2011) showed that when the EBRT was reduced from 120 to 60 s, the NO RE decreased from 95% to 75% because the formation rate of Fe(II)EDTA − NO 2− exceeded the treatment capacity of the microorganisms.…”
Section: Biological Reduction Of No Contained In Iron Chelatesmentioning
confidence: 99%